Trabalho, educação e sujeito: o discurso neoliberal nas publicidades dos Guias das Profissões 2018 e 2019 - Oliveira, Raquel Ribeiro de (2023)
This doctoral thesis is built on two main research questions: "What imaginary formations con(form) meanings about the university and the university subject in the discursive functioning of the advertisements in the special edition Guia das Profissões, published by Abril, 2018 and 2019?" and "How is the discourse about work and education (inscribed) in the imaginary formations and (in) the social division of labor present in Guia das Profissões?". Thus, our corpus consists of 37 advertisements published in the Guia das Profissões 2018 and 2019 printed volumes. In this section, we observed how visibilities and invisibilities are produced, especially through the photographs of the subjects in these advertisements. For the development of this study, French Discourse Analysis (DA) is our main theoretical-methodological anchor, since it is through this device that we develop our work of description, interpretation and analysis of the materialities. In addition to DA, we also reflected on the specificities of photography and advertising, as well as studies on work, education and neoliberalism. By reading, describing and interpreting the selected advertisements, we proceeded to observe the discursive regularities that were present in the corpus. From an analytical reading of the linguistic statements and photographs that make up the advertisements, we arrived at the following regularities: discourses of meritocracy, social inclusion, racial division, competitiveness and success, quality and recognition and happiness. The conditions of production that historically determine the visibility and invisibility of certain subjects in the photographs and the meanings about and for education - and, consequently, about and for work - allow us to reflect on the discursive formations, especially the neoliberal one, in which these statements are inscribed, producing meanings that university is a place for some and not for others. This reflection has enabled us to understand who these (in)visible people are in the publications and the social formation that challenges them in this place of (in)visibility and (non)access. In addition, our analyses allow us to perceive the neoliberal functioning that constitutes and produces the meanings of education and the social division of labor in contemporary times.